Colour psychology in kindergarten classroom - Chin Xing Thung; Hakimi Ahmad (ARTEKS : Jurnal Teknik Arsitektur, 2022)
The research was conducted to explore the colour that can create a calm and peaceful environment in kindergarten classroom. Colour is the mood of a space as each colour has its own meaning. Hence, the colour used in every space need to suit with the activity done in the space. Kindergarten is among many other spaces that used colour a lot because children like colour and will be attracted by colour, especially bright colour. Kindergarten classroom is one of the spaces that preschool children stay in most of time, hence, the colour scheme required careful consideration to calm down children and let them concentrate on learning. From the previous research, it was found that researcher mainly focus on kindergarten design, kindergarten furniture design or on colour design in other interior spaces, such as restaurant, office, and hospital. Hence, the research gap for the will be the colour in the kindergarten classroom which can create a calm and peaceful environment. As there are different colour scheme for interior design, the most suitable colour scheme had identified for the kindergarten classroom to make the preschool children can calm down and pay attention in the classroom. The research concludes that the light green and light blue colour is the ideal colour for a calm and peaceful kindergarten classroom.